A new social contract for technology. Issue 1 (16th November 2022) - Srinivasan, Ramesh; Ghosh, Dipayan
Abstract: The tides of public sentiment in the United States have turned squarely against Silicon Valley's leading internet firms. Long‐running Congressional inquiries; employee‐led backlashes and news leaks; expert analyses that have uncovered deep‐rooted social concerns; and aggressive journalistic inquiry—these and other actions have pushed the executives of America's most successful technology firms under the public microscope. Around the world, there is clear nonpartisan concern about the unaccountable ways that technology companies have invaded personal privacy, threatened the viability of traditional forms of work and the economic welfare they provide to workers, and challenged the backbone of democracy and free press. There seems to be increasing consensus that the commercial internet has become a privately controlled public sphere in which citizens are exposed to a multitude of perspectives all on the same "playing field." This paper's contribution is to argue for the need of a "social contract" for technology—a set of principles that technology corporations and states must adhere to so as to ensure that we overcome the zero‐sum path we are headed to today. 摘要: 美国的舆论潮流已经完全不利于硅谷的领先互联网公司。长期的国会调查、员工引发的强烈反对和新闻泄露、一系列揭示根深蒂固的社会问题的专家分析、以及挑衅的新闻调查——这些和其他行动已将美国最成功的科技公司管理人员推到了公众的检视下。全球都存在明显的无党派关切，聚焦于科技公司以大量方式侵犯个人隐私、威胁传统工作形式的可行性及其为员工提供的经济福利、以及挑战民主和新闻自由。似乎越来越多的共识认为，商业互联网已经成为一个被私人控制的公共领域，在这个领域中，公民在同一个"竞争环境"里接触到多种观点。本文的贡献在于论证了用于技术的"社会契约"的必要性，该社会契约是技术公司和国家必须遵守的一组原则，以确保我们克服当前所走向的零和路径。 Resumen: Las mareas del sentimiento público en los Estados Unidos se han vuelto directamente en contra de las principales empresas de Internet de Silicon Valley. Investigaciones del Congreso de larga duración; reacciones violentas provocadas por los empleados y filtraciones de noticias; análisis de expertos que han puesto al descubierto preocupaciones sociales profundamente arraigadas; y una investigación periodística agresiva: estas y otras acciones han llevado a los ejecutivos de las empresas de tecnología más exitosas de Estados Unidos bajo el microscopio público. En todo el mundo existe una clara preocupación no partidista sobre las formas inexplicables en que las empresas de tecnología han invadido la privacidad personal, amenazado la viabilidad de las formas tradicionales de trabajo y el bienestar económico que brindan a los trabajadores, y desafiado la columna vertebral de la democracia y la libertad de prensa. Parece haber un consenso cada vez mayor de que Internet comercial se ha convertido en una esfera pública controlada de forma privada en la que los ciudadanos están expuestos a una multitud de perspectivas, todas en el mismo "campo de juego". La contribución de este artículo es defender la necesidad de un "contrato social ' para la tecnología: un conjunto de principios que las corporaciones tecnológicas y los estados deben cumplir para garantizar que superemos el camino de suma cero al que nos dirigimos hoy.